Mechanisms of arsenate adsorption by highly-ordered nano-structured silicate media impregnated with metal oxides - Jang, M.; Shin, E.W.; Park, J.K.; Choi, S.I. (2003)
The highly ordered mesoporous silica media, SBA-15, was synthesized and incorporated with iron, aluminum, and zinc oxides using an incipient wetness impregnation technique. Adsorption capacities and kinetics of metal-impregnated SBA-15 were compared with activated alumina which is widely used for arsenic removal. Media impregnated with 10 of aluminum by weight (designated to Al 10SBA-15) had 1.9-2.7 times greater arsenate adsorption capacities in a wide range of initial arsenate concentrations and a 15 times greater initial sorption rate at ph 7.2 than activated alumina. By employing one- and two-site models, surface complexation modeling was conducted to investigate the relationship between the aluminum oxidation states in different media and adsorption behaviors shown by adsorption isotherms and kinetics since the oxidation phase of aluminum incorporated onto the surface of SBA-15 was Al-O, which has a lower oxidation state than activated alumina (Al2O 3). Surface complexation modeling results for arsenate adsorption edges conducted with different pH indicated that the monodentate complex (SAsO42-) was dominant in Al10SBA-15, while bidentate complexes (XHAsO4 and XAsO4-) were dominant in activated alumina at pH 7.2, respectively. In kinetic studies at pH 7.2 Â± 0.02, Al10SBA-15 had only a fast-rate step of initial adsorption, while activated alumina had fast- and slow-rate steps of arsenate adsorption. Therefore, it can be inferred that the monodentate arsenate complex, predominant in Al10SBA-15, leads to faster adsorption rates than bidentate arsenate complexes favored with activated alumina. An arsenate adsorption behavior and arsenate surface complexation were thought to be well explained by aluminum oxidation states and surface structural properties of media.